Development and Validation of Stability-indicating Gas Chromatography Method for the Quantitative Determination of Ethylhexylglycerin and its Impurities in Bulk and Pharmaceutical Dosage Forms - Arla, Rambabu (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: A stability-indicating gas chromatographic flame ionization detection (FID) method for the quantitative determination of ethylhexylglycerin (EHG) and its impurities in drug substance and drug product has been developed and validated. The developed method was also applied to related substances identification in the bulk sample. Materials and Methods: The chromatographic separation was performed on a fused silica capillary (DB-1, 30 m, 0.32 mm, and 0.25 μm film thickness) column, and with a gradient technique. The column oven was programmed as follows: Initial column oven temperature, 60°C; ramped linearly to 280°C at the rate of 8°C/min; hold for 10 min. The runtime of analysis was 30 min. The injector and detector temperature was kept at 240°C and 260°C, respectively. Nitrogen was used as a carrier gas with a constant flow rate of 2 mL/min. The split ratio was set at 20: Results and Discussion: The developed method was validated as per the ICH guidelines. The stability-indicating nature of the method has been proved by establishing peak purity and confirming the mass balance of all samples by subjecting them to stress conditions such as hydrolysis, oxidation, photolysis, and thermal degradation studies. Conclusion: The method was successfully applied to analysis of different bulk sample of EHG and its impurities. The proposed gas chromatography coupled with FID method was also found to be specific and selective for the analysis of commercial formulation samples.